Residential marine field-course impacts on ocean literacy. Issue 7 (2nd July 2020) - Winks, Lewis; Ward, Mark; Zilch, Joseph; Woodley, Ewan
Abstract: Ocean Literacy is a growing global education movement aimed at deepening and contextualising the human relationship with the ocean. While ocean topics are largely missing from UK school curricula, Ocean Literacy principles offer an opportunity for environmental educators to infuse their programmes with broader perspectives on the ocean, creating openings for the development of learner knowledges, and increasing emotional connection with the marine environment. Field courses held at residential field study centres which focus on marine and coastal environments are uniquely positioned to explore principles of Ocean Literacy with their learners; through experiential, investigative modes of learning which encourage development of understanding, emotional engagement with the environment, and pro-environmental behaviours. This paper examines the learning outcomes of 16–18 year old school students taking part in residential programmes at three coastal field centres in the UK Field Studies Council network. Examining student responses against UK A-level, Scottish Highers, and International Baccalaureate specifications and curricula, we argue that while such programmes are largely determined by cognitive rather than behavioural or affective characteristics, they demonstrate a significant opportunity to further develop the emotional and behavioural foci of residential marine courses.